BUDAYA MERTI DESA: INTERNALISASI NILAI KARAKTER DALAM PEMBELAJARAN PPKN DI SEKOLAH DASAR - Budi Safitri, Irma Yulianti; Tri Elitasari, Handara; Rakhmawati, Yeni; Asip, Muhammad (JISPE Journal of Islamic Primary Education, 2022)
Globalization was able to shift the values ​​of nationalism and culture in Indonesia so that students do not understand the Merti Desa tradition. There needs to be an instillation of love for local culture so that it remains sustainable which can be started from students at school. One way was to integrated local cultural wisdom values ​​in schools through the learning process. The value of character education from the Merti Desa ceremony was important to include in Civics learning in addition to increasing children's character values ​​as well as preserving local wisdom culture. This study used library research, namely a series of activities related to library data collection, reading, recording, and processing materials without going through the research field. The author places more emphasis on the power of data analysis and existing data sources by relying on concepts and theories to be interpreted in discussions. The values ​​of character education contained in the Merti Desa tradition included spiritual values, social attitudes, and manners. These values ​​include gratitude to God Almighty, obedience and adherence to what was taught in religion; reflects the attitude of working together to solve common problems and mutual cooperation; appreciate and respect others, and have insight that prioritizes public interests rather than personal interests. Students who have educational character values ​​could follow and interpret the Merti Desa tradition so that they could reintroduce the Merti Desa tradition to the general public and minimize the extinction of the local wisdom of this tradition.